Ugarit and Minoan Crete: The Bearing of Their Texts on the Origins of Western Culture - Gordon, Cyrus H. (1966)
I. Ugarit and Its Significance; II. Ugaritic Literature and Its Greco-Hebrew Affinities; III. Minoan Crete; IV. Ugaritic Poetry; with extensive translations; V. The Prose Texts of Ugarit; VI. Conclusions; $7.50.